Life Cycle Assessment of co-located floating offshore wind and wave energy technologies in Portugal (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Meeting the projected growth in global electricity demand requires innovative and sustainable solutions aligned with net-zero ambitions. Co-located offshore renewable energy (ORE) systems, integrating wave energy converters (WECs) and floating offshore wind turbines (FOW) offer a promising alternative to address space constraints, improve reliability, and reduce environmental impact. This study presents a Life Cycle Assessment (LCA) of a co-located ORE system in Portugal, featuring a 30 MW wave energy array and a 300 MW floating offshore wind farm. Results from a cradle-to-grave evaluation indicate a carbon footprint of 17.7 gCO₂eq/kWh, a carbon payback period (CPBT) of 1.4 years and an energy payback period (EPBT) of 2.0 years. The carbon intensity falls between that of standalone FOW, typically less carbon-intensive, and wave energy, which has higher impacts due to their lower technological maturity and added complexity. By sharing infrastructure and streamlining operation and maintenance (O&M), the co-located system offsets some of the environmental burdens while enhancing the potential of energy production. The findings demonstrate a balanced trade-off between environmental impacts and energy benefits, also underscoring the potential of co-located ORE systems to support the development and commercial readiness of wave energy technologies, fostering innovation and cost reductions.